2014
DOI: 10.1007/978-81-322-1979-8_33
|View full text |Cite
|
Sign up to set email alerts
|

Role of Passion in Organizational Cynicism: A Mediating Effect of Sustainable Leader in the Process Model

Abstract: With the increasing economic turbulence all over the world, it is apparently becoming diffi cult on the part of the corporate to remain as a high-performing organization and intensify the engagement of the employees by keeping enormous pressure to hold down costs as long as market does not show the sign of recovery. Even though the attempt is made to increase one's engagement, one's psychological well-being is always ignored. Moreover, the engagement has always been discussed in the literature of burnout as re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…In addition, studies emphasize the importance of sustainable leadership for forming organizational culture (Morsing & Oswald, 2009) and effective strategic decisions in organizations (Peterlin et al, 2015). In addition, previous literature has shown that sustainable leadership is a critical predictor of organizational cynicism (Gaan, 2015). In addition, in the literature, sustainable leadership mediates the relationship between active participation in organizational decision-making and creative work behavior (Wang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, studies emphasize the importance of sustainable leadership for forming organizational culture (Morsing & Oswald, 2009) and effective strategic decisions in organizations (Peterlin et al, 2015). In addition, previous literature has shown that sustainable leadership is a critical predictor of organizational cynicism (Gaan, 2015). In addition, in the literature, sustainable leadership mediates the relationship between active participation in organizational decision-making and creative work behavior (Wang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…One of the motivational forces behind IWB is harmonious passion, defined as a strong inclination towards the work, which the individual likes and considers important by investing time and energy (Liu et al, 2011). It is considered the highest form of motivation that makes employees perform at their best by showing excitement and energy at work (Gaan, 2015). Research has demonstrated clearly that harmoniously passionate employees are more involved in organisational activities, attract more customers, and perform their duties above average levels (Astakhova, 2015).…”
Section: Introductionmentioning
confidence: 99%